Evaluation of fracture resistance of roots-filled with various root canal sealers at different time periods - Emel Uzunoglu Özyürek; Sevinç Aktemur Türker (Istanbul University, 2019)
Purpose The reinforcement effect of 3 various root canal sealers (AH 26, MTA Plus sealer and BioRoot RCS) and gutta-percha at different time periods (1 week and 1 month) were evaluated in the present study. Materials and Methods Single-rooted, single-canalled, cracks-free 80 mandibular premolars were decoronated to a length of 13mm. Group PC (positive control, n=10): samples were left unprepared and unfilled. Seventy samples were prepared by using the ProTaper Rotary System up to F4. Group NC (negative control, n=10): samples were left unfilled. Remaining 60 samples were assigned into 3 groups; Group 1: AH 26 + F4 gutta-percha (GP); Group 2: MTA Plus sealer + F4 GP and Group 3: BioRoot RCS + F4 GP. Filled samples were divided into subgroups according to storage time: Samples in Groups 1A, 2A, and 3A were stored for 1 week; while Groups 1B, 2B and 3B were stored for 1 month at 100% humidity to allow the complete setting of the sealers (n=10, for each). A universal testing machine at a crosshead speed of 1.0 mm/min was used for fracture testing. For each specimen, the force at the time of fracture was recorded and the data were analyzed statistically. Results The highest fracture resistance values were obtained in Group PC, while the lowest values were obtained in Group NC. Groups PC and NC were statistically different from each other and from other groups, regardless of time (p<0.05). Fracture resistance values of Group AH 26/GP were statistically different from MTA Plus sealer/GP (p<0.05) and were statistically similar with BioRoot RCS/GP, irrespective of time. Within group comparisons revealed that there were no statistically differences between samples filled with same sealer at different time periods. Conclusion Root canal preparation caused decreased fracture resistance. All sealers increased the force values needed to fracture the filled samples compared to unfilled ones. Time factor had no effect on the fracture resistance values.